Efficient near-infrared (NIR) polymer light-emitting diodes (PLEDs) based on heteroleptic iridium(iii) complexes with post-modification effects of intramolecular hydrogen bonding or BF2-chelation. Issue 39 (21st September 2018) - Fu, Guorui; Zheng, Hao; He, Yani; Li, Wentao; Lü, Xingqiang; He, Hongshan
Abstract : Two new heteroleptic iridium(iii )-complexes capable of NIR emission are used to fabricate NIR-PLEDs with high efficiency and almost negligible efficiency-roll-off. Abstract : In heteroleptic iridium(iii )-complexes capable of near-infrared (NIR) emitting, elaboration of their ancillary ligands is under-explored. In this study, through OH-modification at the 3-position of the picolinato (pic) ancillary ligand, we report two new complexes[Ir(iqbt)2 (hpa)] (1 ;Hiqbt = 1-(benzo[ b ]-thiophen-2-yl)-isoquinoline;hpa = 3-hydroxypicolinate) with intramolecular hydrogen bonding and[Ir(iqbt)2 (BF2 -hpa)] (2 ) with further BF2 -chelation, exhibiting desirable NIR luminescent properties ( λ em = 700 nm with a shoulder at 760 nm, lifetime τ = 2.13 μs and quantum yield Φ PL = 0.13 for1 versus λ em = 692 nm with a shoulder at 756 nm, lifetime τ = 0.76 μs and quantum yield Φ PL = 0.08 for2 ) in their respective solutions at RT. Moreover, two series of solution-processed NIR polymer light-emitting diodes (PLEDs-I-II) are fabricated from these two complexes, either in the presence or absence of a TmPyPB-assisted (TmPyPB = 1, 3, 5-tri[(3-pyridyl)-phen-3-yl]benzene) carrier balance, where a superior performance ( η maxEQE = 2.22% and almost negligible efficiency-roll-off) is obtained for complex-1 -doped NIR-PLED-II, with particular respect to facilitated electron transport.